Determination of the residues of lambda cyhalothrin in oil palm agrosystem / Muhammad Zulhilmi Zainal Abidin - Muhammad Zulhilmi , Zainal Abidin (2017)
The objective of this study is to validate the method of detection for lambda cyhalothrin in samples of crude palm and palm kernel oil, soil, leaves and water using gas chromatography-microelectron capture detector (GC-μECD). Based on the establish method, a monitoring study was done in the tropical climate condition of Malaysia to evaluate the dissipation pattern and persistence of lambda cyhalothrin in the oil palm agroecosystem. Our results indicated that the mean recoveries of lambda cyhalothrin were found to be 87-90%, 96-109%, 81-105% and 83-90%, respectively, for crude palm and palm kernel oil, leaves, soil and water sample at three levels of concentrations. The limit of quantification of the method was 0.02 mg/kg, while the limit of detection was 0.002 mg/kg. The monitoring study was conducted at Amcorp Plantation in Sepang, Selangor with three experimental plots of control, recommended dosage and double recommended dosage. The spraying application was conducted in triplicate for each plot involved. Lambda cyhalothrin (ALERT 2.8EC) was sprayed on leaves and at recommended (31.5 g a.i./ha) and double recommended (63 g a.i./ha) manufacturer’s dosage. Samples of oil palm fruits, leaves, soils and water were collected on day 0 (6 hours after spraying), 1, 3, 5, 7, 9, 10, 12, 14, 16, 18, 20 and 29 days after treatment. Initial depositions of lambda cyhalothrin on foliar surfaces were 0.47 and 0.83 mg/kg, at recommended and double recommended dosages respectively. Lambda cyhalothrin residues were not detected after 14 and 18 days of the recommended and double recommended dosages, respectively. No residue was detected in the harvested oil palm fruits, water and soil samples. The half-life (t1/2) value of lambda cyhalothrin was observed to be 3.96 and 4.88 days for recommended and double recommended dosages respectively on leaves of palm oil.